RETRACTED: On the history of the activity of scientific institutions and stations in growing new crop varieties in Uzbekistan - Haitov Jahongir (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001